INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA KANTOR KELURAHAN DI KOTA KUPANG - Alfred T. Rantelobo (P3M- Politeknik Negeri Kupang, 2022)
The purpose of this study to determine community satisfaction index with public services in the Office District of the City Kupang. The community satisfaction index refers to the decision MenPen Number 25/KEP/M.Pan/7/2004 about general guidelines for community satisfaction index government agency service unit. The method used in this study is descriptive quantitative. The sampling technique use accidental samplin techniques. The number of samples in study were 17 the Office District of the City Kupang with were 510 respondens. The technique of collecting data is done by questionnaire. The results showed that the mean community satisfaction index value in the Office District of the City Kupang was 75,23 with the quality being in the B category and GOOD service performance. The Office Noikolan District have the highest community satisfaction index that is to 84 with the quality being in the A category and VERY GOOD service performance. Whereas the Office Pasir Panjang District have the lowest community statisfaction index that is to 68,25 with the quality being in the B category and GOOD service performance